2014
DOI: 10.1186/1745-6215-15-200
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of a randomized controlled trial of esophagectomy for esophageal cancer - the ROMIO (Randomized Oesophagectomy: Minimally Invasive or Open) study: protocol for a randomized controlled trial

Abstract: BackgroundThere is a need for evidence of the clinical effectiveness of minimally invasive surgery for the treatment of esophageal cancer, but randomized controlled trials in surgery are often difficult to conduct. The ROMIO (Randomized Open or Minimally Invasive Oesophagectomy) study will establish the feasibility of a main trial which will examine the clinical and cost-effectiveness of minimally invasive and open surgical procedures for the treatment of esophageal cancer.Methods/DesignA pilot randomized cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 42 publications
0
48
0
1
Order By: Relevance
“…Although we attempted to control for known clinical, socioeconomic, hospital, and tumor covariates through our propensity-matched analysis, inherent differences between comparison groups may still occur that would be best addressed with a sufficiently powered randomized trial. For example, 2 different clinical trials in progress randomizing patients between OE and MIE are the French MIRO (Oesophagectomie Pour Cancer par Voie Conventionnelle ou Coelio-Assistée) trial [18] and the British ROMIO (Randomized Oesophagectomy: Minimally Invasive or Open) trial [19]. Nonetheless, our study is the largest comparative effectiveness study of MIE to date to examine long-term survival.…”
Section: Commentmentioning
confidence: 99%
“…Although we attempted to control for known clinical, socioeconomic, hospital, and tumor covariates through our propensity-matched analysis, inherent differences between comparison groups may still occur that would be best addressed with a sufficiently powered randomized trial. For example, 2 different clinical trials in progress randomizing patients between OE and MIE are the French MIRO (Oesophagectomie Pour Cancer par Voie Conventionnelle ou Coelio-Assistée) trial [18] and the British ROMIO (Randomized Oesophagectomy: Minimally Invasive or Open) trial [19]. Nonetheless, our study is the largest comparative effectiveness study of MIE to date to examine long-term survival.…”
Section: Commentmentioning
confidence: 99%
“…The three meta-analyses built on these randomized trials showed no diference in survival when the endpoint was 1-year survival in six of these trials. On the contrary, in comparison with surgical treatment, 2-year survival rates were improved following preoperative chemotherapy (4.4%) when the endpoint was 2-year survival in seven randomized trials [53]. When the meta-analysis was restricted to four recently randomized trials based on cisplatin and 5-luorouracil therapy, there was a 6.3% improvement in 2-year survival.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 93%
“…These limitations pave the way for the occurrence of unknown interactions and confounding variables. Currently, there are two diferent clinical trials comparing E to MIE patients, namely the French MIRO trial [52] and the British ROMIRO trail [53]. Still, the study that we conducted is the most extensive comparative efectiveness research of MIE assessing long-term survival.…”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…These include development of a typology with which to deconstruct interventions into component parts (in order to consider which may need to be standardized), and qualitative data collection in the operating room (in order to understand how interventions are actually delivered and explore surgeons' views about standardization). 42 The methods are currently being tested and refined within an RCT 34 and observational study, 43 to explore how the interventions might be described and standardized across different research settings.…”
Section: Selecting and Standardizing Interventions And Determining Tmentioning
confidence: 99%
“…Case study 2 Achieving blinding of patients: the ROMIO study 34,46 Background Surgery alone or in combination with chemotherapy or chemoradiation treatment is the mainstay of cure for localized esophageal cancer. There are several surgical approaches, and the past decade has seen a growing interest in minimal access surgical techniques with the potential advantages of causing less tissue trauma and better recovery.…”
Section: Rct = Randomized Controlled Trialmentioning
confidence: 99%